2014
DOI: 10.1155/2014/491398
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Canadian Respiratory Clinical Trials from 2001 to 2011

Abstract: Clinical research bridges patients' unmet medical need with innovative medicines, increases knowledge acquisition by clinicians, and creates solutions to improve the sustainability and quality of the Canadian health care system and economy. The Canadian Institutes of Health Research and the Canadian Lung Association have recently raised concerns over declining research activities within the Canadian respiratory community. While there are currently >3000 ongoing clinical trials in Canada, the number of trials i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
0
4
0
Order By: Relevance
“…We achieve these 2 objectives by comparing ClinicalTrials.gov data to a well-established and widely used information source: Informa Pharma Intelligence’s Trialtrove database. 29 Trialtrove is a commercially available resource, first introduced in 2004, that draws data on clinical trials from more than 70 country, regional, and multi-national trial registries in addition to trial listings from biopharmaceutical companies, registries published by patient advocacy groups, and clinical trials presented at major medical meetings and in medical journals. 30,31 This baseline assessment will prove useful in future assessments of ClinicalTrials.gov post January 18, 2017.…”
Section: Introductionmentioning
confidence: 99%
“…We achieve these 2 objectives by comparing ClinicalTrials.gov data to a well-established and widely used information source: Informa Pharma Intelligence’s Trialtrove database. 29 Trialtrove is a commercially available resource, first introduced in 2004, that draws data on clinical trials from more than 70 country, regional, and multi-national trial registries in addition to trial listings from biopharmaceutical companies, registries published by patient advocacy groups, and clinical trials presented at major medical meetings and in medical journals. 30,31 This baseline assessment will prove useful in future assessments of ClinicalTrials.gov post January 18, 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Although sublingual immunotherapy tablets (SLIT-T) have been in use in Europe for several years, the experience with Timothy grass immunotherapy tablet in Canadian and US subjects is limited. Given the prevalence of AR in Canada [ 2 ] and the relatively small number of AR clinical trials conducted in Canada from 2001 to 2011 [ 13 ], it was of interest to determine if SLIT-T would reduce AR symptoms and medication use in Canadian participants. The efficacy and safety of the Timothy grass 2800 BAU SLIT-T, which dissolves within seconds [ 14 ], has been investigated in 3 North American trials in which it was found to be effective and well tolerated for participants with grass-pollen–induced AR/C [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thankfully, in the past several years the numbers have increased and, in 2010/2011, an average of 61 respiratory trials per year were conducted in Canada, with an average of 16 per year being conducted independent of industry. Reassuringly, Tacon et al (1) found that the number of respiratory clinical trials conducted in Canada has increased at an average rate of 4.5 per year over the past decade.…”
mentioning
confidence: 99%
“…In summary, the study by Tacon et al (1) suggests that our relatively terrible performance at the start of the millenium has improved this past decade, and more Canadian investigators and Canadian patients, have the opportunity to participate in respiratory and critical care clinical trials of new medicines and new treatment procedures. However, there are threats on the horizon.…”
mentioning
confidence: 99%